PENERAPAN METODE SIMPLE ADDITIVE WEIGHT (SAW) DALAM SISTEM PENDUKUNG KEPUTUSAN PROMOSI KENAIKAN JABATAN - Frieyadie, Frieyadie (Jurnal Pilar Nusa Mandiri, 2016)
HR management of a company greatly affect many aspects of determining the success of the work of the company. One very important process in the Human Resources Department (HRD) a company or entity that is the promotion of a promotion. In general, the promotion was given on the recommendation boss or work unit each based on the old work, the performance assessment and assessment of the behavior of an employee in performing their duties. For that it is necessary appraisal data processing employees who can help facilitate a supervisor and the human resources department to take a decision relating to the promotion of an employee promotions. Currently the company employee appraisal data processing is still performed with computerized excel, so the greater the risk of inputting errors given the number of employees very much and and it takes a relatively long time. It is also still often confusing information regarding the movement of formation of employees. The method used in determining promotion This promotion is Simple Additive Weight (SAW). Where this method is a weighted counting method or methods that provide certain criteria are weighted so that each value of the sum of the weights of the obtained results will be the final decision. Judging from the managerial aspects of the assessment can be developed with other criteria in accordance with the company's needs. Calculations using Simple Additive Weight, with reference to the criteria of employment, performance evaluation, and assessment of employee behavior, then elect an employee who will get promotion.